Thermodynamic calculations in ternary titanium-aluminium-manganese system - Kostov Ana I.; Živković Dragana T. (Journal of the Serbian Chemical Society, 2008)
Thermodynamic calculations in the ternary Ti-Al-Mn system are shown in this paper. The thermodynamic calculations were performed using the FactSage thermochemical software and database, with the aim of determining thermodynamic properties, such as activities, coefficient of activities, partial and integral values of the enthalpies and Gibbs energies of mixing and excess energies at two different temperatures: 2000 and 2100 K. Bearing in mind that no experimental data for the Ti-Al-Mn ternary system have been obtained or reported. The obtained results represent a good base for further thermodynamic analysis and may be useful as a comparison with some future critical experimental results and thermodynamic optimization of this system.